The effect of educational program based on the health belief model in adopting dental caries preventive behaviour’s in pregnant mothers referring to health treatment centers in Ardabil - Abbasgholizadeh, Nategh; Moradi-asl, Eslam; Abazari, Malek; Adham, Davoud (International Journal of Advances in Medicine, 2019)
Background: Oral and dental diseases are one of the most common diseases and oral hygiene is one of the important branches of public health which is more important during pregnancy. This study aimed to determine the effect of the educational intervention on oral health behaviours in pregnant mothers. Methods: In this intervention study, 170 pregnant women in the city of Ardabil were randomly selected and divided into two case and control groups (each of 85 people). The data were collected through a researcher-made questionnaire based on the Health Belief Model of oral health care and then they were analysed using the SPSS version 19. Results: Demographic data in both case and control groups were approximately the same. The mean of health belief model variables increased significantly after intervention (P 0.05). Mothers also obtained the most information on the prevention of dental caries before intervention through television programs but after the intervention, they obtained the most information through the curriculum. In this study, before the intervention, 23.7% of mothers used dental floss once a day. After training, this amount reached 40.8% of mothers. Conclusions: Findings showed that educational intervention based on the health belief model can promote oral health behaviours. Therefore, it is recommended to conduct health education courses at the community level.